Measuring scarce water saving from interregional virtual water flows in China. (27th April 2018) - Zhao, X; Li, Y P; Yang, H; Liu, W F; Tillotson, M R; Guan, D; Yi, Y; Wang, H
Abstract: Trade of commodities can lead to virtual water flows between trading partners. When commodities flow from regions of high water productivity to regions of low water productivity, the trade has the potential to generate water saving. However, this accounting of water saving does not account for the water scarcity status in different regions. It could be that the water saving generated from this trade occurs at the expense of the intensified water scarcity in the exporting region, and exerts limited effect on water stress alleviation in importing regions. In this paper, we propose an approach to measure the scarce water saving associated with virtual water trade (measuring in water withdrawal/use). The scarce water is quantified by multiplying the water use in production with the water stress index (WSI). We assessed the scarce water saving/loss through interprovincial trade within China using a multi-region input-output table from 2010. The results show that interprovincial trade resulted in 14.2 km 3 of water loss without considering water stress, but only 0.4 km 3 scarce water loss using the scarce water concept. Among the 435 total connections of virtual water flows, 254 connections contributed to 20.2 km 3 of scarce water saving. Most of these connections are virtual water flows from provinces with lower WSI to that with higher WSI. Conversely, 175 connections contributed to 20.6 km 3 of scarce water loss. The virtual water flow connections between Xinjiang and other provinces stood out as the biggest contributors, accounting for 66% of total scarce water loss. The results show the importance of assessing water savings generated from trade with consideration of both water scarcity status and water productivity across regions. Identifying key connections of scarce water saving is useful in guiding interregional economic restructuring towards water stress alleviation, a major goal of China's sustainable development strategy.